Experimental investigation and design of sheathed LSF wall panels under eccentric axial compression. (July 2022) - Peiris, Mithum; Mahendran, Mahen
Abstract: Sheathing is an important component in cold-formed Light gauge Steel Framed (LSF) walls and floors. LSF wall studs with one- or two-sided sheathing have been shown to have an increased ultimate compression capacity since the sheathing is capable of restraining global buckling modes. Although sheathing's contribution has been ignored in the past, current design standards include provisions for the consideration of sheathing in the design of LSF walls. Australian cold-formed steel standard allows the designers to consider sheathing's lateral and rotational restraints to studs, but it does not quantify the restraint values to be used. A recent report of American Iron and Steel Institute (AISI RP 13-1) provides suitable design guidelines for LSF walls with single sheathing, non-identical sheathing and different fastener spacings subject to axial compression, however, they have not been validated for LSF walls under combined compression and bending actions. An experimental investigation on LSF wall panels subject to combined actions due to eccentric loading was conducted in this research to understand the effects of loading eccentricity on sheathed LSF wall panels. Fifteen single stud wall panels of 1.5 m and 3.0 m height made of lipped channel studs were tested under concentric and major axis eccentric compression loading. Effects of sheathing and loading eccentricity on the failure modes and ultimate capacities were evaluated, and importantly, the suitability of the sheathing braced design guidelines in AISI RP 13-1 was investigated. The results showed that the use of the spring-based restraints recommended in AISI RP 13-1 with the linear interaction equation provides improvements in predicting the capacity of sheathed walls subject to eccentric compression. Highlights: Conducted 15 concentrically and eccentrically loaded tests of gypsum plasterboard sheathed LSF walls. Investigated the effects of loading eccentricity, sheathing thickness, screw spacing and stud geometry on wall stud capacity. Demonstrated the applicability of linear interaction equation in the sheathed braced design of LSF wall studs. Ignoring the sheathing effect significantly underestimated the capacity of LSF walls. AISI sheathing braced design method was able to predict the capacities of sheathed LSF walls under eccentric compression.